Prophages of the genus Bifidobacterium as modulating agents of the infant gut microbiota. (18th January 2016) - Lugli, Gabriele Andrea; Milani, Christian; Turroni, Francesca; Tremblay, Denise; Ferrario, Chiara; Mancabelli, Leonardo; Duranti, Sabrina; Ward, Doyle V.; Ossiprandi, Maria Cristina; Moineau, Sylvain; van Sinderen, Douwe; Ventura, Marco
Summary: Phage predation is one of the key forces that shape genetic diversity in bacterial genomes. Phages are also believed to act as modulators of the microbiota composition and, consequently, as agents that drive bacterial speciation in complex bacterial communities. Very little is known about the occurrence and genetic variability of (pro)phages within the B ifidobacterium genus, a dominant bacterial group of the human infant microbiota. Here, we performed cataloguing of the predicted prophage sequences from the genomes of all currently recognized bifidobacterial type strains. We analysed their genetic diversity and deduced their evolutionary development, thereby highlighting an intriguing origin. Furthermore, we assessed infant gut microbiomes for the presence of (pro)phage sequences and found compelling evidence that these viral elements influence the composition of bifidobacterial communities in the infant gut microbiota.